Sosialisasi Olahraga Rekreatif Sebagai Wujud Kearifan Lokal Di Kabupaten Tana Toraja Utara - Muhammad Ilham; Budyanita Asrun; Rusandy (Yayasan Habiburrahman Jamalu Bina Ummat, 2022)
The development of Tana Toraja Regency into one of the potential tourist destinations and Convention Centers on a national, regional, and international scale, thus making this district have to start equipping itself with various facilities that can support the existence of Tana Toraja Regency as a tourist and convention destination. The supporting facilities include the Healthcare Facility, which is needed by tourists and convention participants, as well as local communities to maintain/maintain stamina as well as recreation/relaxation. One of the health facilities that can fulfill the Preventive Healthcare Service theme is the Outdoor Recreational Sports Center, where various facilities are provided in this building that can support the activities of health care and human fitness. The most common thing people do to maintain a healthy body is to exercise. Today, sports activities have been combined with recreational activities, because in sports, there are also elements of recreation and relaxation